Razlike med cestnimi in gorskimi kolesarji v izhodnih spremenljivkah odnosa sila-hitrost-moč pri skokih z dodatnimi bremeni - Spudić, Darjan (Šport (Ljubljana), 2023)
The aim of our study was to examine the differences in the squat jump height and the output variables of the Force-Velocity- Power (F-v-P) relationship between elite road, enduro, and downhill mountain bikers. The F-v-P relationship was measured during squat jumps with a barbell for 32 cyclists. Participants performed jumps with four different loading conditions - determined relative to the participants’ body mass. Analysis of variance showed statistically significant differences between cycling disciplines (road, downhill, enduro) in jump height (p < 0.001) and maximum theoretical power (Pmax ) (p < 0.05). Enduro cyclists generated greater Pmax and jumped higher than road cyclists and downhill mountain bikers (p < 0.05). The results of the elite cyclists in our study provide reference values for strength and power training of leg extensors among young cyclists. Based on the results, we recommend leg extensor power training aimed at increasing Pmax , especially for enduro cyclists.
Keywords: cestno kolesarstvo; enduro; gorsko kolesarstvo; hitra moč; spust; šport